2014
DOI: 10.1007/s00417-014-2746-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sulodexide in patients with non-proliferative diabetic retinopathy: diabetic retinopathy sulodexide study (DRESS)

Abstract: PurposeTo evaluate the effectiveness of sulodexide for the treatment of hard exudates (HE) in non-proliferative diabetic retinopathy (NPDR).MethodsThis was a randomized, placebo-controlled, multicenter trial involving 130 patients (65 for each group) who had mild-to-moderate NPDR with macular HE. Participants were given a daily dose of either 50 mg sulodexide or a matching dose of placebo orally for 12 months. Main outcome measure was an improvement in HE defined as a decrease in severity by at least two grade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 21 publications
1
17
0
2
Order By: Relevance
“…Song et al (DRESS study group) conducted a clinical trial with a similar design to our study and suggested that oral sulodexide, which is a highly purified glycosaminoglycan (GAG), showed a significant decrease in HEs in patients with mild to moderate NPDR, with central foveal thickness ≤300 μm. [19] Based on previous animal study, [24] they presumed that oral sulodexide may repair endothelial damage due to diabetes and normalize the vascular permeability and GAG metabolism, resulting in resorption of HEs. They reported that oral sulodexide did not show significant differences in central retinal thickness compared to the placebo group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Song et al (DRESS study group) conducted a clinical trial with a similar design to our study and suggested that oral sulodexide, which is a highly purified glycosaminoglycan (GAG), showed a significant decrease in HEs in patients with mild to moderate NPDR, with central foveal thickness ≤300 μm. [19] Based on previous animal study, [24] they presumed that oral sulodexide may repair endothelial damage due to diabetes and normalize the vascular permeability and GAG metabolism, resulting in resorption of HEs. They reported that oral sulodexide did not show significant differences in central retinal thickness compared to the placebo group.…”
Section: Discussionmentioning
confidence: 99%
“…[18] This grading system for HE severity has been used in a previously published clinical trial from our group. [19] We used this grading system without modification. Briefly, this grading system was based on the area of retina involved by HE and the amount of HE observed; the ETDRS standard photographs 3 and 4 were used for comparison.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, sulodexide has other pharmacological effects potentially useful in the diabetic patients, subject to a high probability of developing acute cardiovascular diseases: anti-thrombotic activity, decrease of oxidative stress, hypolipidemic effect, prevention of glucose toxicity, suppression of cellular inflammation and anti-atheromatous effects [6]. Several clinical studies demonstrated sulodexide efficacy in patients, diabetic and not diabetic, affected by vascular diseases associated with a thrombotic risk: peripheral occlusive arterial diseases [29,30], prevention of recurrent deep venous thrombosis [31,32], diabetic retinopathy [33], diabetic foot [34,35], cerebrovascular [36,37] and cardiovascular diseases [38,39] and management of chronic venous disease, including the more severe and complicated cases such as venous ulcers [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…A phase II randomized controlled trial evaluated the effects of oral therapy with a glycosaminoglycan (GAG), sulodexide (Vessel Due F, Aju Pharm, Seoul, South Korea, under license from Alfa Wassermann, Bologna, Italy), on hard exudates in patients with NPDR, and reported a significant reduction in these exudates compared with placebo [95]. The premise for this clinical trial was that in diabetic retinopathy, similar to diabetic nephropathy, GAGs are replaced by collagen in the retinal capillary basement membrane, leading to changes in the permeability of these capillaries [95,96].…”
Section: Proliferative Diabetic Retinopathy (Pdr) and Nonproliferativmentioning
confidence: 99%
“…The premise for this clinical trial was that in diabetic retinopathy, similar to diabetic nephropathy, GAGs are replaced by collagen in the retinal capillary basement membrane, leading to changes in the permeability of these capillaries [95,96]. Currently, the role of dietary supplements such as alpha-lipoic acid and multicomponent nutritional capsules in the management of NPDR are also being evaluated in a number of clinical trials [97,98].…”
Section: Proliferative Diabetic Retinopathy (Pdr) and Nonproliferativmentioning
confidence: 99%